Median ilmaisuvoimaisuus pörssiyhtiöiden sijoittajille suunnatussa viestinnässä - Koskela, Merja (VAKKI ry, 2018)
Inspired by the development of digital communication, listed companies are constantly developing new ways to serve and attract interested audiences on their Investor Relations websites. This paper focuses on the types and variety of multimodal semiotic resources employed on Investor Relations websites of Finnish listed companies with specific focus on the use of videos. The aim of the paper is to explore how videos are used, what form they take and which affordances they offer as a presentation form from the perspective of financial communication. The data is derived from the IR websites of three Finnish industrial companies. The results of the study show that the three companies have somewhat different numbers of videos on their IR websites, but the most common type of video, a webcast announcing periodic results of the companies is the same for all companies. The webcasts seem to have an established format combining audio, still pictures or video with PowerPoint slides embedded on the websites, indicating that a hybrid genre is developing. Video is used as part of the webcasts because it allows a rhetorical use of nonverbal cues, such as tone of voice, gestures and facial expressions, targeted focus and clarity of language. These are features of a rich communication medium generating affect, delivering an image of openness and creating trust and thus potentially influencing decisions. However, two central features of rich media, the degree of interaction and possibility of feedback are limited because they cannot easily be controlled by the company.
Keywords: median ilmaisuvoimaisuus; verkkosivut; sijoittajaviestintä; media; WWW-sivut; video; fi=Viestintätieteet|en=Communication Studies|